Efficient base editing for multiple genes and loci in pigs using base editors - Jingke Xie (Nature Portfolio, 2019)
Base editors can efficiently produce single nucleotide alterations without requiring a double-strand break. Here the authors show base editing at multiple sites simultaneously in pigs.